Analysis of the Effect of the Probability Ratio on Sharia Stock Return (Study on the List of Undelisting Sharia Stocks in the Jakarta Islamic Index December 2014-2018) - Sari, Nilam; Fachrurrozi, Kamal; Rizqy, Irhas (SCAD Independent, 2022)
This research was conducted to determine the effect of Return On Assets, Return On Equity, and Earning Per Share on Sharia Stock Returns in Indonesia. The data used in this study comes from the Indonesia Stock Exchange for the 2014-2018 period. The method used was descriptive statistical analysis and Fixed Effect Model (FEM) panel regression analysis. The results of this study indicated that partially the Return On Asset variable had a negative and significant effect on Sharia Stock Return. While the variables Return On Equity and Earning Per Share partially had a positive and significant effect on Sharia Stock Return. Then, simultaneously the variables Return On Asset, Return On Equity, and Earning Per Share had a positive and significant effect on Sharia Stock Return.